Searching for the Achilles Heel of FOXP3 - Lozano, Teresa; Casares, Noelia; Lasarte, Juan J. (Frontiers in Oncology, 2013)
FOXP3 is a multifaceted transcription factor with a major role in the control of immune homeostasis mediated by T regulatory cells (Treg). The immunoregulatory function of FOXP3 may hinder the induction of immune responses against cancer and infectious agents, and thus, development of inhibitors of its functions might give new therapeutic opportunities for these diseases. But also, FOXP3 is an important tumor suppressor factor in some types of cancers, and therefore, understanding the structure and function of FOXP3 is crucial to gaining insights into the development of FOXP3-targeted therapeutic strategies. FOXP3 homodimerize and likely form supramolecular complexes which might include hundreds of proteins which constitute the FOXP3 interactome. Many of the functions of FOXP3 are clearly regulated by the interactions with these cofactors contributing importantly on the establishment of Treg-cell signature. We summarize here the structural/functional information on this FOXP3 complex, to identify potential opportunities for the development of new strategies to modulate FOXP3 activity.